2020
DOI: 10.3390/ijms21217934
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Sugarcane Response to Aluminum Stress by RNA-Seq

Abstract: Some metals are beneficial to plants and contribute to critical physiological processes. Some metals, however, are not. The presence of aluminum ions (Al3+) can be very toxic, especially in acidic soils. Considerable parts of the world’s arable land are acidic in nature; mechanistically elucidating a plant’s response to aluminum stress is critical to mitigating this stress and improving the quality of plants. To identify the genes involved in sugarcane response to aluminum stress, we generated 372 million pair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Mechanistically elucidating a plant's response to Al stress is critical to mitigating this stress and improving the quality of plants. To identify the genes involved in sugarcane response to Al stress, Rosa-Santos and colleagues [36] generated 372 million paired-end RNA sequencing reads from the roots of CTC-2 and RB855453, which are two contrasting cultivars. The majority of the genes were upregulated in the CTC-2 (tolerant cultivar) and downregulated in RB855453 (sensitive cultivar).…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Mechanistically elucidating a plant's response to Al stress is critical to mitigating this stress and improving the quality of plants. To identify the genes involved in sugarcane response to Al stress, Rosa-Santos and colleagues [36] generated 372 million paired-end RNA sequencing reads from the roots of CTC-2 and RB855453, which are two contrasting cultivars. The majority of the genes were upregulated in the CTC-2 (tolerant cultivar) and downregulated in RB855453 (sensitive cultivar).…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Next-generation sequencing (NGS), particularly RNA-seq is a highly effective tool for generating high quality transcriptome sequence reads in several crops such as Eleusine coracana (Parvathi et al, 2019), oat (Avena sativa; (Kim et al, 2022), sugar cane (Saccharum officinarum; (Rosa-Santos et al, 2020) and Japanese carpet shell (Ruditapes philippinarum; (Nie et al, 2017). However, no transcriptome-based research has been published on finger millet in association with Al-tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Altolerance based transcriptomic analysis generated 495 differentially expressed genes, of which 322 genes were significantly differentially expressed between Al-tolerant and Al-susceptible finger millet genotypes. These are a large number of genes although they are fewer than 6165 Al-stress responsive DEGs identified in sugarcane (Rosa-Santos et al, 2020), and 1790 drought responsive DEGs identified in finger millet (Parvathi et al, 2019) using RNA-seq. Due to the use of leaf tissue instead of root tissue for the transcriptome analyses, there may have been fewer significant DEGs identified in this study, indicating that leaves are less responsive to the effects of Al.…”
Section: Differentially Expressed Genesmentioning
confidence: 99%
“…In recent years, RNA sequencing (RNA-seq) has emerged as an indispensable tool for transcriptome analysis because it can generate a vast number of reads, providing a comprehensive overview of the transcriptomic landscape. Consequently, RNA sequencing has been applied to investigate Al response mechanisms in various plant species, including Pinus massoniana [42], sugarcane [43], aspen [44], peanut [45], and alfalfa [46], uncovering numerous physiological and metabolic processes involved in Al stress such as oxidative stress, organic acid exudation, defense against cell wall toxicity, and hormone signal transduction. Despite extensive information on Al stress responses, the specific mechanisms via which melatonin regulates Al toxicity in alfalfa remain unexplored.…”
Section: Of 17mentioning
confidence: 99%